The role of SPRTN protease in colorectal cancer chemotherapy - Peron, C (2023)
Colorectal cancer (CRC) currently represents one of the most commonly diagnosed tumors, accounting for 10% of all cancer diagnoses and cancer-related deaths. The first-line treatment of metastatic colorectal cancer (mCRC) is frequently based on combination chemotherapeutic regimens, where 5-fluorouracil is either associated with irinotecan (FOLFIRI) or oxaliplatin (FOLFOX). Both these regiments present similar level of efficacy, and both irinotecan and oxaliplatin have been reported as drugs with the potential to induce relevant amounts of DNA-protein crosslinks (DPCs), a heterogeneous form of DNA lesion in which proteins end up being covalently bound to the DNA. At the moment we are currently lacking reliable methods to predict which patients are more likely to respond to FOLFIRI or FOLFOX, which would allow us to choose the most appropriate therapy for each patient. In order to address this need, the role of SPRTN in colorectal cancer chemotherapy is investigated for the first time in this thesis.